Enhanced visual performance in obsessive compulsive personality disorder. Issue 6 (22nd July 2016) - Ansari, Zohreh; Fadardi, Javad Salehi
Abstract : Visual performance is considered as commanding modality in human perception. We tested whether Obsessive–compulsive personality disorder (OCPD) people do differently in visual performance tasks than people without OCPD. One hundred ten students of Ferdowsi University of Mashhad and non‐student participants were tested by Structured Clinical Interview for DSM‐IV Axis II Personality Disorders (SCID‐II), among whom 18 (mean age = 29.55; SD = 5.26; 84% female) met the criteria for OCPD classification; controls were 20 persons (mean age = 27.85; SD = 5.26; female = 84%), who did not met the OCPD criteria. Both groups were tested on a modified Flicker task for two dimensions of visual performance (i.e., visual acuity: detecting the location of change, complexity, and size; and visual contrast sensitivity). The OCPD group had responded more accurately on pairs related to size, complexity, and contrast, but spent more time to detect a change on pairs related to complexity and contrast. The OCPD individuals seem to have more accurate visual performance than non‐OCPD controls. The findings support the relationship between personality characteristics and visual performance within the framework of top‐down processing model.